Innovation in Mathematics Learning through The Use of Straws and Number Pockets with A Differentiated Learning Approach - Choirul Umam Mujaddi; Nur Fazria Masfufah; Mochammad Ashabul Yamin; Maryam Isnaini Damayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Low student interest in Mathematics, particularly in addition and subtraction operations, has resulted in low participation and learning outcomes that do not meet the Minimum Mastery Criteria (MMC) of 80. This study aims to improve students’ learning outcomes through the use of Strawsand number pocket learning media. This research employed a Classroom Action Research (CAR) design conducted in two cycles involving 28 first-grade students. Data were collected through learning evaluations and classroom observations. The results showed a significant improvement in students’ achievement. In the first cycle, 46.43% of students achieved mastery with an average score of 76.25. This increased to 85.71% in the second cycle, with an average score of 83.71. These findings indicate that Straws and number pocket media effectively enhance students’ understanding and problem-solving skills in basic arithmetic operations.